Unveiling the frontiers of potato disease research through bibliometric analysis - Weng, Ling; Tang, Zhurui; Sardar, Muhammad Fahad; Yu, Ying; Ai, Keyu; Liang, Shurui; Alkahtani, Jawaher; Lyv, Dianqiu (Frontiers in Microbiology, 2024)
Research on potato diseases had been widely reported, but a systematic review of potato diseases was lacking. Here, bibliometrics was used to systematically analyze the progress of potato disease. The publications related to "potato" and "disease" were searched in the Web of Science (WOS) from 2014 to 2023. The results showed that a total of 2095 publications on potato diseases were retrieved, with the annual publication output increasing year by year at a growth rate of 8.52%. The main countries where publications were issued were the United States, China, and India. There was relatively close cooperation observed between China, the United States, and the United Kingdom in terms of international collaboration, while international cooperation by India was less extensive. Based on citation analysis and trending topics, potential future research directions include nanoparticles, which provides highly effective carriers for biologically active substances due to their small dimensions, extensive surface area, and numerous binding sites; machine learning, which facilitates rapid identification of relevant targets in extensive datasets, thereby accelerating the process of disease diagnosis and fungicide innovation; and synthetic communities composed of various functional microorganisms, which demonstrate more stable effects in disease prevention and control. In conclusion, this study systematically analyzed the progress of potato disease research, providing insights for the prevention and control of potato diseases.